2020
DOI: 10.3168/jds.2019-17919
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and biofilm formation potential of Bacillus subtilis and Bacillus velezensis in extended shelf-life milk processing line

Abstract: This study aims to characterize Bacillus subtilis complex group from raw, pasteurized, and packaged extended shelf-life (ESL) milk samples, to determine their biofilm potential and source-track the microbial contaminants to control their presence during processing. Isolates were characterized using multi-locus sequence typing (MLST) with 7 housekeeping genes. The primers used were designed from the coding regions with the highest number of polymorphic sites. The heat resistance profile indicated that all 12 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Figure 4a indicated that the BS could form biofilm on the solid surface after 24 h of interaction. The OD570 value at 24 h was 3.2 ± 0.2 which was close to the value of 3.14 ± 0.60 of the B. velezensis LPL-K103 (Elegbeleye, Buys, 2020). Besides checking for bacterial adherence ability, the effect of various environmental factors on the growth of BS strain was also carried out in this study.…”
Section: Probiotic Characteristics Of B Velezensis Grew In the Sbm-co...supporting
confidence: 69%
“…Figure 4a indicated that the BS could form biofilm on the solid surface after 24 h of interaction. The OD570 value at 24 h was 3.2 ± 0.2 which was close to the value of 3.14 ± 0.60 of the B. velezensis LPL-K103 (Elegbeleye, Buys, 2020). Besides checking for bacterial adherence ability, the effect of various environmental factors on the growth of BS strain was also carried out in this study.…”
Section: Probiotic Characteristics Of B Velezensis Grew In the Sbm-co...supporting
confidence: 69%
“…Of all carriers, P (spherical filter material made of polyester fiber) showed the best performance. Thick cell layer was observed on the surface of P. It has been reported that the high degree of hydrophobicity strongly enhances adhesion of microorganisms ( Silva-Dias et al, 2015 ; Elegbeleye and Buys, 2020 ). An additional aspect worthy of consideration is that iturin A secreted by Bacillus velezensis ND have relatively high amphiphilic ( Meena and Kanwar, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…have the ability to form biofilms with intricate structures, and this process is regulated by complex pathways. Elegbeleye and Buys (2020) assessed the biofilm formation potential of the isolated strains and observed that some of them exhibited moderate to strong biofilms. The strain specificity of the biofilm structure was also observed in our study.…”
Section: Discussionmentioning
confidence: 99%